2024
DOI: 10.3390/plants13050590
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic, Nutritional and Sensory Characteristics of Bakery Foods Formulated with Grape Pomace

Andrea Antoniolli,
Lucía Becerra,
Patricia Piccoli
et al.

Abstract: The potentiality of cv. Malbec grape pomace (GP) as a functional ingredient in the formulation of bakery foods (muffins, biscuits and cereal bars) was studied. The effect of GP addition on the phenolic compounds (PCs) composition, nutritional and sensory properties were evaluated. The addition of GP increased the content of dietary fiber, proteins, ash, total phenolic content (TPC), antiradical capacity (AC), anthocyanins and non-anthocyanin PCs while decreasing the carbohydrates content. The main PCs given by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In addition to its nutritional importance, grape pomace extract can certainly be utilized as a functional component in foods and beverages to provide health benefits [65,[74][75][76], as can be observed in Table 3. The influence of grape pomace powder on the chemical, technological, and sensory characteristics of muffins was assessed by Troilo et al [65], Baldán et al [74], and Antoniolli et al [77]. These studies concluded that grape pomace powder added to muffins can enhance their nutritional value by increasing the content of bioactive compounds (e.g., phenolic compounds, anthocyanins), as evidenced by the positive results obtained in the analysis of muffins and the acceptance of products containing grape pomace by consumers [65,74,77].…”
Section: Functional Ingredients In Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its nutritional importance, grape pomace extract can certainly be utilized as a functional component in foods and beverages to provide health benefits [65,[74][75][76], as can be observed in Table 3. The influence of grape pomace powder on the chemical, technological, and sensory characteristics of muffins was assessed by Troilo et al [65], Baldán et al [74], and Antoniolli et al [77]. These studies concluded that grape pomace powder added to muffins can enhance their nutritional value by increasing the content of bioactive compounds (e.g., phenolic compounds, anthocyanins), as evidenced by the positive results obtained in the analysis of muffins and the acceptance of products containing grape pomace by consumers [65,74,77].…”
Section: Functional Ingredients In Foodsmentioning
confidence: 99%
“…The influence of grape pomace powder on the chemical, technological, and sensory characteristics of muffins was assessed by Troilo et al [65], Baldán et al [74], and Antoniolli et al [77]. These studies concluded that grape pomace powder added to muffins can enhance their nutritional value by increasing the content of bioactive compounds (e.g., phenolic compounds, anthocyanins), as evidenced by the positive results obtained in the analysis of muffins and the acceptance of products containing grape pomace by consumers [65,74,77]. Milinčić et al [76] investigated the physical and functional qualities of goat milk powders enhanced with grape pomace seed extract, and the results demonstrated that thermally treated enriched goat milk powders exhibited improved emulsifying properties and stability, making them promising ingredients for the formulation of functional food that require good emulsifying activity and stability.…”
Section: Functional Ingredients In Foodsmentioning
confidence: 99%